UPAYA RAINFOREST RESOURCE AND DEVELOPMENT CENTRE (RRDC)DALAM MENANGANI DEFORESTASI HUTAN DI CROSS RIVER NIGERIA - Widyana, Niken Retno; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Nigeria possesses tropical forests that have undergone extensive deforestation, particularly in the Cross River region. The palm oil industry has displaced forests that hold vital significance for the global environment. Efforts to address the resulting impacts have prompted the involvement of the Rainforest Resource and Development Centre (RRDC) to mitigate the issue. The initiatives undertaken by RRDC in combating forest deforestation in Cross River are discussed in detail in this study. This research employs a qualitative approach based on secondary data, using document analysis from books, national and international journals, official reports of international institutions, and news articles. The analysis of the NGO’s role refers to John McCormick’s theoretical perspective. The findings reveal that RRDC’s strategies include collaborating with elected officials, bureaucrats, and corporate employees; conducting campaigns and organizing public protests; enhancing media engagement and environmental awareness; and pursuing litigation as well as monitoring the enforcement of environmental laws. Overall, this study highlights the significant role of local NGOs in promoting environmental justice and governance, particularly in efforts to reduce corporate-driven deforestation in developing countries such as Nigeria. Keywords: Rainforest Resource and Development Centre (RRDC), Non-Governmental Organization, Deforestation, Wilmar International Limited, Cross River,Nigeria.